Search for an Astronomical Site in Kenya (SASKYA) update: Installation of on-site automatic meteorological stations. (March 2015) - Graham, Edward; Vaughan, Richard; Buckley, David; Tirima, Koi
Abstract: At present, there are few large telescopes (1-metre diameter mirror or larger) in subSaharan Africa, and the objective of the Search for an Astronomical Site in Kenya ("SASKYA") project has been find the best possible sites in Kenya for such an observatory. An initial study using ERA-interim reanalyses and high resolution meteorological model output identified three preferential sites, based on a selection of thirteen candidate mountain peaks across Kenya. These three sites are Mount Kulal (2.72°N, 36.93°E, 2293m); OlDonyoNyiro (2.09°N, 36.85°E, 2752m) and Warges (0.95°N, 37.40°E, 2688m). Recently (as of Spring 2014), an automatic meteorological station has been installed on the summit of Warges mountain, but security issues have prevented the installation of one on Mount Kulal. Furthermore, at the former site, the lack of suitable roadway through the heavily forested mountain-side will probably preclude further investigation. Hence, an additional but lower site, near to Warges (Ololokwe mountain, 0.83°N, 37.53°E, 1920m), which has a road to the summit, will be investigated for suitability in the near future. Following a period of successful meteorological observation at either or all of the above-mentioned sites, comparison and validation studies will be enacted using climate reanalyses. If further funding permits, all-sky cameras will be installed and high resolution EUMETSAT satellite imagery will also be consulted to determine local cloudiness coefficients.